Abnormal nuclear expression of Pygopus‐2 in human primary hepatocellular carcinoma correlates with a poor prognosis. Issue 2 (12th February 2015) - Zhang, Sheng; Li, Jie; He, Fei; Wang, Xiao‐Min
<x xml:space="preserve">Abstract</x> Aims Pygopus‐2 (Pygo2) is a critical element of the canonical Wnt/β‐catenin transcriptional complex. The aim of the present study was to investigate the expression patterns and clinicopathological significance of Pygo2 in human primary hepatocellular carcinoma (HCC). Methods and results Real‐time polymerase chain reaction (PCR) analysis of the mRNA levels of Pygo2 in 50 paired HCC cancer/adjacent non‐cancerous tissues showed that Pygo2 mRNA expression was significantly higher in cancerous tissues (P = 0.009). Immunohistochemical analysis showed that abnormal Pygo2 protein expression in HCC patients was associated with age (P = 0.025), tumour size (P = 0.005), intra‐ or extra‐hepatic metastasis (P = 0.029), vascular invasion (P = 0.026) and tumour differentiation (P = 0.004). Patients with normal Pygo2 protein expression showed a longer survival time (P = 0.031) and a higher 1‐year survival rate (P = 0.032) than those with abnormal Pygo2 expression. Cox's proportional hazard regression model showed that abnormal Pygo2 protein expression was a risk factor associated with the prognosis of HCC patients (P = 0.043). Conclusion To the best of our knowledge, this is the first report investigating Pygo2 expression patterns and their clinicopathological significance in HCC. Our findings suggest that Pygo2 may be an important predictor of poor outcome in HCC patients, and could serve as a novel biomarker for HCC.